Notes on Early Land Plants Today. 18. Transfers of some taxa in Nardia (Gymnomitriaceae, Marchantiophyta) - Váňa, Jiří; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2013)
In recent years, molecular studies have shown that characters associated with reproduction (sexual as well as asexual) are much more important in separating taxa at higher level than generally believed 10-15 years ago. For example, the color of gemmae (red or yellow) is a character separating Lophozia (Dumortier 1831: 53) Dumortier (1835: 17) s.str. from Lophoziopsis Konstantinova & Vilnet (2010: 66) (De Roo et al. 2007, Vilnet et al. 2011). Also, the presence and absence of a perigynium is shown to separate the two genera Jungermannia Linnaeus (1753: 1131) and Solenostoma Mitten (1865: 51), two genera that have mostly been treated as congeneric over the last 25-30 years (see Váňa & Long 2009).